Intrapersonal predictors of internalized stigma among school going adolescents living with HIV in southwestern Uganda. - Kirabira, Joseph; Ashaba, Scholastic; Favina, Allain; Maling, Samuel; Nansera, Denis; Zanoni, Brian C. (Kirabira, J., Ashaba, S., Favina, A., Maling, S., Nansera, D., & Zanoni, B. C. (2022). Intrapersonal predictors of internalized stigma among school going adolescents living with HIV in southwestern Uganda.medRxiv ., 2022)
Background: HIV is one of the most stigmatized conditions globally significantly affecting the quality of life of people living with HIV. Stigma particularly affects adolescents living with HIV (ALHIV) due to challenges associated with developmental stage including physical and psychological changes and the need to build peer relationships. The effect of intrapersonal factors including resilience, health locus of control, self-efficacy, and empowerment on HV stigma among ALHIV in Uganda has not been studied. This study aimed at assessing the association between internalized HIV stigma and resilience, health locus of control, coping self-efficacy and empowerment among ALHIV. Methods: We conducted a cross-sectional study between August and October 2020 among 173 adolescents who were attending the HIV clinic at Mbarara Regional Referral Hospital. We measured HIV stigma (the internalized AIDS Related Stigma scale), health locus of control (the 18-item Form C version of the Multi-Dimensional Health Locus of Control measure), resilience (25-item Resilience Scale), self-efficacy (the coping self-efficacy scale), and empowerment (the 28-item empowerment scale). Linear regression models were run to determine the association between HIV stigma and intrapersonal factors and adjusted for sociodemographic characteristics. Results: The median age of participants was 16 (IQR 15-18) years and the median HIV stigma score was 3 (IQR 2-4). There was a negative correlation between HIV stigma and internal health locus of control (b= -0.08, p<0.001), resilience (b= -0.03p<0.001) and coping self-efficacy (b= -0.02, p<0.001) while empowerment score was positively correlated (b= 0.05, p=0.003). However, after mutually adjusting for the intrapersonal factors (resilience, internal locus of control, empowerment and coping self-efficacy), and sociodemographic characteristics, only internal health locus of control (p=0.008) and coping self-efficacy (p<0.001) remained significantly associated with HIV stigma. Conclusion: Internal health locus of control, resilience, coping self-efficacy and empowerment are strong intrapersonal predictors of internalized stigma among ALHIV. Designing interventions focusing on strengthening these factors among the adolescents may be a significant step in the fight against internalized HIV stigma
Keywords: HIV stigma; Self-efficacy; Empowerment; Resilience; Locus of control; Uganda